Estimating public agricultural expenditure requirements - Benin, Samuel; Fan, Shenggen; Johnson, Michael E. (International Food Policy Research Institute, 2012)
This chapter outlines an approach to estimating the public agricultural financial resources needed to bring about a certain rate of agricultural growth. Studies that estimate the public financial resources required to achieve specific development objectives have focused on costing the Millennium Development Goals (MDGs). Public agricultural financial resources needed to achieve specific agricultural development objectives or broader targets are dealt with indirectly in a few studies only.